Improvements in Depressive Symptoms and Affect During Cardiac Rehabilitation: PREDICTORS AND POTENTIAL MECHANISMS. Issue 1 (January 2019) - Gathright, Emily C.; Busch, Andrew M.; Buckley, Maria L.; Stabile, Loren; DeAngelis, Julianne; Whited, Matthew C.; Wu, Wen‐Chih
Abstract : Purpose: Depression is indicative of poor prognosis in cardiac patients. Reductions in depression have been observed following cardiac rehabilitation (CR). Whether similar improvements in positive and negative affect occur is unknown. Greater understanding of depressive symptom and affect change is needed to enhance facilitators of emotional improvement after a cardiac event. Methods: Cardiac rehabilitation attendees (n = 637) completed measures of depressive symptoms, affect, health status, and social support at CR intake and discharge. Body mass index, metabolic equivalents, and blood pressure were also measured. Relationships between changes in psychosocial and physical health indicators and depressive symptoms, positive affect, and negative affect were examined. Results: From intake to discharge, depressive symptoms ( d = 0.40, P < .001) and negative affect ( d = 0.26, P < .001) decreased. Positive affect increased ( d = 0.34, P < .001). In multivariate regression, predictors of depressive symptom reduction were increased vitality (β = −.26) and decreased bodily pain (β = −.08). Predictors of positive affect increase were increased vitality (β = .25), social support (β = .16), and physical role functioning (β = .09). Predictors of negative affect reduction were increased vitality (β = −.23) and social support (β = −.10). Changes in indicators of physical health were not related to depressive symptom or affect change. Conclusions: Depressive symptom and affect improvements following CR were observed and most strongly associated with improvements in vitality and social support. Future research should explore how enhancement of these mechanisms may further improve depressive symptom and affect during CR. Abstract : Increased understanding of contributors to depressive symptom and affect improvement following cardiac rehabilitation (CR) is needed. A sample of 637 participants completed assessments of depressive symptoms, affect, social support, health, and clinical outcomes at CR intake and discharge. Improved vitality and social support contributed to depressive symptom and affect change.